Edukasi Kesehatan Berbasis Pengalaman Skrining dalam meningkatkan kesadaran lansia terhadap penyakit tidak menular - Winda Afikirtiani; Ichwan Muslimin; Citra Della; Khoirunnisa Rahma; Laura antika; Selfi Mey; Ida Ayu; Putri Sheila; Septi Wulan; Olif Delfia (Yayasan Inspirasi El Burhani, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement aimed at integrating the Tri Dharma of Higher Education through the direct application of knowledge in society. This Akhlakul Karimah KKN program was conducted in Dusun 3, Pekon Wonosari, Gadingrejo District, Pringsewu Regency, focusing on improving elderly health through health screening and education on non-communicable diseases. The main issues identified were the high prevalence of hypertension and diabetes mellitus among the elderly and low awareness of routine health check-ups. The program methods included health screening through blood pressure and blood glucose measurements, health education, and evaluation of participants’ understanding. The results showed increased elderly participation in health screening activities, improved knowledge regarding hypertension and diabetes mellitus, and early detection of abnormal health conditions that required referral to healthcare facilities. This program demonstrates that an educative and participatory community-based approach is effective in improving elderly health awareness and self-care.